Nanoparticles Based on Star Polymers as Theranostic Vectors: Endosomal-Triggered Drug Release Combined with MRI Sensitivity - Li, Y.; Duong, H.; Laurent, S.; MacMillan, A.; Whan, R.; Elst, L.; Muller, R.; Hu, J.; Lowe, Andrew; Boyer, C.; Davis, T. (Wiley - V C H Verlag GmbH & Co. KGaA, 2015)
Dual-functional star polymers (diameters 15 nm) are synthesized producing nanoparticles with excellent colloidal stability in both water and serum. The nanoparticles are built with aldehyde groups in the core and activated esters in the arms. The different reactivity of the two functional groups to sequentially react with different amino compounds is exploited; doxorubicin (DOX) and 1-(5-amino-3-aza-2-oxypentyl)-4,7,10-tris(tert-butoxycarbonylmethyl)-1,4,7,10-tetraazacyclododecane (DO3A-tBu-NH2)—a chelating agent effective for the complexation of Gadolinium ions (Gd). The activated ester group is employed to attach the DO3A chelating agent, while the aldehyde groups are exploited for DOX conjugation, providing a controlled release mechanism for DOX in acidic environments. DOX/Gd-loaded nanoparticles are rapidly taken up by MCF-7 breast cancer cells, subsequently releasing DOX as demonstrated using in vitro fluorescence lifetime imaging microscopy (FLIM). Endosomal, DOX release is observed, using a phasor plot representation of the fluorescence lifetime data, showing an increase of native DOX with time. The MRI properties of the stars are assessed and the relaxivity of Gd loaded in stars is three times higher than conventional organic Gd/DO3A complexes. The DOX/Gd-conjugated nanoparticles yield a similar IC50 to native DOX for breast cancer cell lines, confirming that DOX integrity is conserved during nanoparticle attachment and release.